2020
DOI: 10.3390/diagnostics10090651
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myocarditis-Like Episode in a Curly-Haired Young Boy—Red Flags for Familial Arrhythmogenic Cardiomyopathy

Abstract: The present case report describes a mother and son with arrhythmogenic cardiomyopathy (ACM) with early and greater left ventricle (LV) involvement. The presence of curly hair in both, together with the resuscitated sudden cardiac death of the mother, allowed timely genetic testing, which found a pathogenic nonsense mutation of the desmoplakin gene. While asymptomatic from an arrhythmic point of view, the son’s evolution was characterized by a well-documented exercise-induced myocarditis-like stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The initial suspicion of acute myocarditis or myocardial infarction has later led to a diagnosis of left-dominant or biventricular ACM ( 20 , 39 42 ). These episodes have sometimes been associated with exercise ( 18 , 19 , 43 ). Similar to our findings, other studies have found that 15%–20% of DSP variant carriers had experienced an episode of myocardial injury presenting with acute chest pain and troponin elevation ( 18 , 34 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial suspicion of acute myocarditis or myocardial infarction has later led to a diagnosis of left-dominant or biventricular ACM ( 20 , 39 42 ). These episodes have sometimes been associated with exercise ( 18 , 19 , 43 ). Similar to our findings, other studies have found that 15%–20% of DSP variant carriers had experienced an episode of myocardial injury presenting with acute chest pain and troponin elevation ( 18 , 34 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that DSP cardiomyopathy could be considered a distinct form of cardiomyopathy ( 18 ). In addition to the cutaneous features, patients have been reported to have episodes of myocardial inflammation, sometimes provoked by exercise ( 18 , 19 ). These inflammatory episodes might be confused with myocarditis of other etiologies, which might delay diagnosis ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%